STUDENTS’ PERCEPTIONS TOWARD THE USE OF MOBILE LEARNING IN LEARNING ENGLISH - Alan Jaelani; Siti Dairotul Rahmah (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2019)
This study aims at investigating students’ perceptions toward the use of mobile learning (m-learning) in learning English and of the effects itself. This study uses qualitative as a framework for analyzing and collecting the data. The data were obtained from questionnaire and interview. The data were analyzed through transcribing, coding and interpreting. This study reveals that the majority of students have positive perceptions on the use of m-learning; students may easily access useful material by using mobile devices; m-learning help students increase flexibility of learning inside and outside classroom because they can easily get learning materials anywhere and anytime. Most of the students perceive that the use of m-learning can improve their English skills and enable them to independent learning.